Dampak Ekonomi Pemberian Nanokapsul Ekstrak Kulit Manggis sebagai Feed Additive Fitogenik pada Broiler Terinfeksi Avian Pathogenic E. coli - Kusmayadi, Andri; Sundari, Ristina Siti; Sujana, Endang (Universitas Galuh, 2026)
Avian Pathogenic Escherichia coli (APEC) infection poses a significant challenge in intensive broiler farming, as it compromises production performance and increases treatment costs. Meanwhile, phytogenic feed additives derived from natural ingredients such as mangosteen peel are gaining attention as safer and more sustainable alternatives. Nanocapsule technology enables efficient release of active compounds, but its economic feasibility requires systematic evaluation. This study aims to assess the economic impact of using mangosteen peel extract nanocapsules as a phytogenic feed additive in broilers infected with APEC. The analysis was conducted using Income Over Feed Cost (IOFC), Break-Even Value (BEV), and sensitivity simulations based on feed price and biological performance. Results indicate that the additive improves feed efficiency and profit margins, especially under carcass-based marketing scenarios. Simulations yielded economically viable thresholds for active ingredient pricing (P_aBE and P_EFE), which vary according to efficiency levels and market conditions. This approach offers a practical framework for farmers to design adaptive, efficient, and sustainable feed formulations.